2014
DOI: 10.4028/www.scientific.net/amm.660.317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Die Gap and Punch Travel on Springback in Air V-Bending Process Using Taguchi Method

Abstract: Springback is a serious problem for the manufacturing industry due to error in the appearance of the final product especially in bending process. Therefore, it's important to investigate the factors that affect the springback behavior . This paper focused on the effect of two parameters, namely die gap and punch travel on springback behavior in air V-die bending process for stainless steel sheet metal. Different values of die gap and punch travel were experimentally used and the final bent angle was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…5-7. Since this model have mixed level of parameters, 0.7418 is possible for this study and coincide with analysis done by Buang et al [14]. …”
Section: Regression Analysismentioning
confidence: 62%
“…5-7. Since this model have mixed level of parameters, 0.7418 is possible for this study and coincide with analysis done by Buang et al [14]. …”
Section: Regression Analysismentioning
confidence: 62%
“…Effects of various factors on springback have been analyzed by ANOVA techniques. The result showed that the punch travel is more significant factor than die gap [25].…”
Section: Factors Affecting Springbackmentioning
confidence: 73%
“…Researchers have developed metal bending rebound prediction models for compensating the CNC bending parameters 8 11 There are many factors that affect the amount of rebound, including the size, shape, thickness, material, and structure of workpieces, as well as manufacturing parameters 12 , 13 . The bending rebound model cannot cover all of the factors affecting rebound at the same time.…”
Section: Introductionmentioning
confidence: 99%